Effects of Psoralen on Histone‐DNA Interactions Studied by Using Atomic Force Microscopy. Issue 24 (19th July 2020) - Zhang, Yingqi; Zhang, Xiaonong; Zhang, Wei; Zhang, Wenke
Abstract: The investigation of the DNA‐histone interactions and factors that affect such interactions in the nucleosome is essential for understanding the role of chromatin organization in all cellular processes involved in the repair, transcription, and replication of the eukaryotic genome. As a kind of photosensitive molecule, psoralen (PSO) is used in the treatment of skin disease with ultraviolet light (PSO and ultra violet light, type A). The effect of treatment is remarkable, but the side effect is also obvious. PSO can be embedded in a 5′ TA sequence in double‐stranded DNA (dsDNA), and dsDNA is mainly wrapped around a histone octamer to form a nucleosome structure in human cells. Therefore, it is very necessary to explore the influence of PSO on DNA‐histone interactions. To this end, the binding specificity and mode of DNA and histone in the presence or absence of PSO are investigated systematically. The results show that the presence of PSO (no matter if there is ultra violet light treatment) can increase the overall probability of histone binding to dsDNA while lowering the selectivity of histone binding to the specific DNA sequence in vitro. In addition, the increase of solution ionic strength can lower the ratio of histone binding to nonspecific DNA. Abstract : Effects of psoralen (PSO) on histone‐DNA interactions are studied by using atomic force microscopy imaging. It is found that the presence of PSO can increase the overall probability of histone binding to double‐stranded DNA while lowering the selectivity of histone binding to the specific DNA sequence in vitro. High salt can disassembly the complexes formed by a nonspecific sequence.